Barley microRNAs as metabolic sensors for soil nitrogen availability - Grabowska, Aleksandra; Smoczynska, Aleksandra; Bielewicz, Dawid; Pacak, Andrzej; Jarmolowski, Artur; Szweykowska-Kulinska, Zofia (Plant science (Limerick), 2020)
•13 barley microRNAs and 2 microRNAs* are nitrogen excess responsive.•Target mRNA levels are in agreement with the cognate microRNA level change.•Identified microRNAs and their targets respond in an opposite way in nitrogen deficiency conditions.•These microRNAs can be regarded as sensors of nitrogen homeostasis in barley plants. Barley (Hordeum vulgare) is one of the most important crops in the world, ranking 4th in the worldwide production. Crop breeders are facing increasing environmental obstacles in the field, such as drought, salinity but also toxic over fertilization which not only impacts quality of the grain but also an yield. One of the most prevalent mechanisms of gene expression regulation in plants is microRNA-mediated silencing of target genes. We identified 13 barley microRNAs and 2 microRNAs* that are nitrogen excess responsive. Four microRNAs respond only in root, eight microRNAs only in shoot and one displays broad response in roots and shoots. We demonstrate that 2 microRNAs* are induced in barley shoot by nitrogen excess. For all microRNAs we identified putative target genes and confirmed microRNA-guided cleavage sites for ten out of thirteen mRNAs. None of the identified microRNAs or their target genes is known as nitrogen excess responsive. Analysis of expression pattern of thirteen target mRNAs and their cognate microRNAs showed expected correlations of their levels. The plant microRNAs analyzed are also known to respond to nitrogen deprivation and exhibit the opposite expression pattern when nitrogen excess/deficiency conditions are compared. Thus, they can be regarded as metabolic sensors of the regulation of nitrogen homeostasis in plants.